Wellbeing and national identity in three generations of Czech and Slovak Holocaust survivors - Preiss, Marek; Fňašková, Monika; Nečasová, Markéta; Heissler, Radek; Bob, Petr; Prokopová, Alice; Šamánková, Dita; Sanders, Edel; Rektor, Ivan (Frontiers in behavioral neuroscience, 2022)
Subjective wellbeing (SWB) is an important factor of global adjustment. Intergenerational satisfaction in seriously traumatized people has not been studied so far in homogenous populations of Central and Eastern Europe. This study focuses on the SWB in three generations of survivors living in the Czech Republic and Slovakia after World War II (WWII). The focal groups were Holocaust survivors (ages 71-95, n = 47), Holocaust survivors' children (ages 30-73, n = 86), and their grandchildren (ages 15-48, n = 88), and they were compared to aged-matched groups without Holocaust history. The first and second generation of Holocaust survivors scored significantly lower than the comparison groups in wellbeing, as measured using the Schwartz Outcome Scale-10 (SOS-10). There was no significant difference in life satisfaction in any of the three generations. Within the focal group, identification as Jewish or as also Jewish was comparable in all three generations of Holocaust survivors (74% in the first, 79% in the second, and 66% in the third generation). Holocaust survivors declaring Jewish identity reported lower SWB compared to survivors declaring other than Jewish identity. The focal group generated more national identities than comparisons. The outcomes are discussed in the context of the history of Central and Eastern Europe.
Keywords: Czech; trauma; transgenerational; PTSD; Holocaust